Effect of Mung Bean Peel on the Internal Organ of Male Bali Ducks - J. R., Nainggolan; Siti, N W.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2019)
Research aimed to determine the effect of using peel mung bean in the diet on the internal organ in male bali duck aged 8 weeks. The design used was completely randomized design (CRD), which consists of three treatments, namely: P0 (ration commercially without mung bean peel), P1 (rations containing 6% of mung bean peel), and P2 (rations containing 12% mung bean peel). Each treatment consisted of 5 replications and each replication using 3 male bali ducks aged 3 days with an average weight 42.9 ± 1.98 g. The variables measured are weight and percentage of the heart, liver, proventriculus, ventriculus, and bile. The results showed that ration containing 6 % and 12 % mung bean peel had no significant effect (P> 0.05) on all weights and percentages organs. Based on the results of this study it can be concluded that bali duck given of mung bean peel at a level of up to 12% did not affect on weight and percentage of internal organs (heart, liver, proventriculus, ventricles, and bile) bali duck male aged 8 weeks.   Keywords: internal organ, male bali ducks, green bean sprout peels flour